2021
DOI: 10.1088/1402-4896/abdb58
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing spatially varying optical emissions in a steady-state dipole plasma: inversion based experiments and modeling

Abstract: This study characterizes spatially varying optical emissions in a compact dipole plasma device driven at steady-state by continuous mode microwaves. The study is motivated by visual observations, which indicate a distinct pattern of alternate bright and less bright regions (bearing structural resemblance to the two particle radiation belts found in the Earth's magnetosphere). The investigation is performed in two experimental systems of cylindrical and spherical geometries, and boundary effects in the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…They also considered a Maxwellian EEDF to be a good first approximation in their model. Thus, our current investigation confirms the consideration of Maxwellian distribution in [41][42][43]74]. Radial variation of (a) effective electron neutral collision rates (νen) and ionization rate (ν i ) in direction parallel to the magnetic field using method-I (solid curves) and II (dashed curves) in the polar plane.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…They also considered a Maxwellian EEDF to be a good first approximation in their model. Thus, our current investigation confirms the consideration of Maxwellian distribution in [41][42][43]74]. Radial variation of (a) effective electron neutral collision rates (νen) and ionization rate (ν i ) in direction parallel to the magnetic field using method-I (solid curves) and II (dashed curves) in the polar plane.…”
Section: Discussionsupporting
confidence: 85%
“…This two-way investigation of thermalization as a result of random walk leading to a Maxwellian distribution, and the random walk leading to a classical diffusion seems to suggest that our observation of the Maxwellian plasma supports the claim of classical diffusion in the dipole plasma. Moreover, in [74], the authors have shown that the radial variation of normalized local emissivity ϵ(r) of the dipole plasma showed a global broad high emission region around r = 3-9 cm due to a peak in the plasma density (N e ) in that region, and a rapid decline in emissivity ϵ(r) after r = 9 cm. They also considered a Maxwellian EEDF to be a good first approximation in their model.…”
Section: Discussionmentioning
confidence: 99%